1989
DOI: 10.1002/mus.880120208
|View full text |Cite
|
Sign up to set email alerts
|

Calcium currents and asymmetric charge movement in malignant hyperpyrexia

Abstract: In both control pigs and pigs susceptible to malignant hyperpyrexia (MH), the size of the calcium current (ICa) and the amount of asymmetric charge movement varied considerably between different gracilis muscle fibers but appeared to vary in parallel. The mean amount of both ICa and charge movement were slightly but significantly smaller in MH-susceptible (MHS) muscle compared with normal muscle. Halothane (1% v/v) reduced both parameters by almost 50%. One interpretation of the data is that the signal, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…2 and Table II). In an earlier study describing charge movements in swine R615C Hom fibers, Lamb et al (1989) did not observe a shift in charge movement. Recently, however, Andronache et al (2009) reported a hyperpolarizing shift of ∼5 mV in charge movements of Y522S Het fibers.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…2 and Table II). In an earlier study describing charge movements in swine R615C Hom fibers, Lamb et al (1989) did not observe a shift in charge movement. Recently, however, Andronache et al (2009) reported a hyperpolarizing shift of ∼5 mV in charge movements of Y522S Het fibers.…”
Section: Discussionmentioning
confidence: 72%
“…2) is probably one contributor to the reduction in [ΔF/F] max . Interestingly, Lamb et al (1989) also found a reduction in Q max (∼20%) in swine R615C Hom gracilis fibers. Moreover, Andronache et al (2009) found an ∼10% reduction in Q max in Y522S Het interosseus fibers.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, our group observed about a 7 mV hyperpolarizing shift in L-type current activation for mouse myotubes homozygous for the engineered R163C mutation [96]. Hyperpolarizing shifts in charge movement have also been observed for both R163C myotubes [96] and Y522S fibers [95], but not in swine R165C myotubes [97]. In regard to EC coupling, each of these malignant hyperthermia models [R163C, Y522S, R615C; 94-96,98,99] and dyspedic myotubes expressing RyR1 constructs carrying a number of different malignant hyperthermia-linked mutations [100] have also displayed hyperpolarizing shifts in SR Ca 2+ release in response to depolarization suggesting that RyR1 malignant hyperthermia mutations shift the equilibrium of Ca V 1.1 towards the state(s) active for EC coupling and L-type channel activation.…”
Section: Cav11 Channel Properties Are Atypically Dependent On Conformentioning
confidence: 88%
“…Although the concentration of thymol is relatively low (0.01 %) in the original halothane-thymol mixture [17], its concentration may dramatically increase due to accumulation of thymol in the vaporizer. Indeed, halothane was shown to block Ca and K currents in cardiac [18-20] and skeletal [21] muscle membranes. These effects, obtained with liquid halothane (containing also thymol) in various preparations, strongly resemble the present results and also those of Magyar et al obtained in canine cardiac cells with thymol [9].…”
Section: Discussionmentioning
confidence: 99%